Measurement and QCD analysis of double-differential inclusive jet cross sections in pp collisions at s = 8 $$ \backslashsqrt{s}=8 $$ TeV and cross section ratios to 2.76 and 7 TeV - CMS Collaboration, CMS; Ibrahim, Z. A.; Komaragiri, J. R.; Md. Ali, Mohd. Adli; Mohamad Idris, F.; Wan Abdullah, W. A. T.; Yusli, M. N.; Zolkapli, Z. (Springer Verlag, 2017)
A measurement of the double-differential inclusive jet cross section as a function of the jet transverse momentum p T and the absolute jet rapidity |y| is presented. Data from LHC proton-proton collisions at s = 8 $$ \backslashsqrt{s}=8 $$ TeV, corresponding to an integrated luminosity of 19.7 fb−1, have been collected with the CMS detector. Jets are reconstructed using the anti-k T clustering algorithm with a size parameter of 0.7 in a phase space region covering jet p T from 74 GeV up to 2.5 TeV and jet absolute rapidity up to |y| = 3.0. The low-p T jet range between 21 and 74 GeV is also studied up to |y| = 4.7, using a dedicated data sample corresponding to an integrated luminosity of 5.6 pb−1. The measured jet cross section is corrected for detector effects and compared with the predictions from perturbative QCD at next-to-leading order (NLO) using various sets of parton distribution functions (PDF). Cross section ratios to the corresponding measurements performed at 2.76 and 7 TeV are presented. From the measured double-differential jet cross section, the value of the strong coupling constant evaluated at the Z mass is α S(M Z)þinspace=þinspace0.1164 −þinspace0.0043 +þinspace0.0060 , where the errors include the PDF, scale, nonperturbative effects and experimental uncertainties, using the CT10 NLO PDFs. Improved constraints on PDFs based on the inclusive jet cross section measurement are presented.